New museums - Barreneche, Raúl A.
The twenty-first century has ushered in a boom in the design of innovative museums worldwide and an expanding concept of the museum´s role and identity. New Museums presents a selection of 27 notable museums built around the world in recent years, each distinguished by its unique architectural design and function. Included are the Schaulager in Basel, by Herzog + de Meuron; the Nasher Sculpture Center in Dallas, Texas, by Renzo Piano; the Great Court at the British Museum in London, by Foster + Partners; and Horiyuji Treasures Gallery in Tokyo, by Yoshio Taniguchi, among others